QRIS Media for Advanced MSMEs: Analysis of Factors Affecting the Use Using Technology Acceptance Model - Tarigan, Bahagia; Rokhmat, Rokhmat; Widodo, Kristianto Purwoko; Endang Wijayanti, Lilis (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this article is to determine user perceptions regarding payments with QRIS. The users in question are MSMEs. The analysis was carried out using the technology acceptance model. The Technology Acceptance Model analyzes perceptions of an application based on perceived ease and perceived usefulness. The research object is MSME actors in the DIY area. Data was obtained by distributing questionnaires to MSME actors in the Yogyakarta area. The number of questionnaires processed was 138 questionnaires. Data analysis uses Moderating Regression Analysis. The research results show that Perception of Convenience and Perception of Usefulness influence the use of QRIS for MSMEs.